EP 5. Decrement of the effect of neuromuscular electrical stimulation over time in chronic stroke patients. Issue 9 (September 2016) - Quandt, F.; Feldheim, J.; Loitz, J.C.; Wolff, D.; Rohm, M.; Rupp, R.; Krautschneider, W.H.; Hummel, F.C.
Abstract : Background: Neuromuscular electrical stimulation (NMES) has been applied as one rehabilitative treatment option in stroke patients (Quandt and Hummel, 2014 ) and a meta-analysis recently showed its positive effects on motor recovery (Stein et al., 2015 ). One major challenge in stroke patients, especially severely impaired, is the opening of the hand due to extensor weakness accompanied by flexor spasticity. Here, NMES could provide assistance and substitute lost function. Studies in healthy controls have shown, however, that the rapid onset of muscle fatigue is a critical limitation for practical use. Here, we measure muscle fatigue over time during repetitive NMES in stroke patients and evaluate the impact of NMES on spasticity. Methods: NMES was applied in a heterogeneous group of 7 chronic stroke patients (FM μ = 34/66, ran 13–51, ARAT μ = 13/57, ran 3–34) with different degrees of spasticity (MAS 0–4) over the extensor digitorum muscles using the MotionStim8, controlled via PC (25 Hz, 25 mA, 200–300 μs). The protocol comprised 6 blocks of stimulation with increasing pulse width (50 μs). Each block consisted of 10 alternating 10 s rest and 10 s stimulation periods. The next block was initiated 3 min later. To measure the impact of stimulation on finger extension, but not on wrist movement, stimulation was combined with an orthosis to stabilize the wrist. Effect of stimulation on finger movement was measured using a force gauge and a bend sensor. The median of the relative stimulation effect (stimulation period – following rest period) was taken and data were normalized between 0 and 1 to allow for comparison across patients. Statistical significance was assessed by modeling a simple linear regression for each patient. The regression coefficients β I were tested in a Students t -test against zero. Results: The stimulation induced strength and movement showed a significant reduction over time (force, p = 0.004, sensor deviation, p = 0.017), even though pulse width was increased (Fig. 1 ). Moreover, a reduction was already detected within a block. Even though a slight recovery occurs after the 3-minute break, break time was not sufficient to recover and reduce muscle fatigue completely. Spasticity of the flexor muscle was reduced after stimulation as measured by the MAS ( μ pr ä = 2.6, μ post = 1.6, p = 0.05). Conclusion: The effect of NMES on force production and finger extension did significantly decrease over a short period of time. The immediate decline after few hand openings critically underlines the need for measures to reduce muscle fatigue. Increased muscle fatigue during NMES compared to physiological movement could be a result of synchronous fiber stimulation and attempts of spatially distributed stimulation have been made to reduce fatigue in healthy controls (Sayenko et al., 2014 ).